Legalitas Perjanjian Tidak Tertulis Arisan Online Ditinjau Dalam Kitab Undang-Undang Hukum Perdata - Nasution, Adawiyah; Maulana, Farrel; qonita, Haya (Universitas Ekasakti, 2023)
Online saving club is a group of people who use social media as a tool to raise money regularly at any given period. Saving club is recognized as an agreement even though it is often done. This online gathering is only done by agreement between several parties who participate in the gathering and is not written. If in the future there are problems such as defaults, it is very difficult to prove the form of the agreement is not written so that to resolve the problem, including the recognition of the parties participating in the social gathering. For this reason, this study will discuss what exactly is the position of the verbal agreement electronically and how its legal force is and what legal remedies are taken in the event of a breach of contract. This research was conducted by reviewing and focusing on the application of